Dynamic expression patterns of ATF3 and p53 in the hippocampus of a pentylenetetrazole-induced kindling model - DING, DONG-XUE (D.A. Spandidos, 2014)
Epilepsy is a common and often deleterious neurological condition. Emerging evidence has demonstrated the roles of innate immunity and the associated inflammatory processes in epilepsy. In a previous study, we found that Toll-like receptors (TLRs) are upregulated and promote mossy fiber sprouting (MFS) in an epileptic model. As downstream effectors of TLRs, the activating transcription factor 3 (ATF3) and p53 proteins were shown to be involved in neurite outgrowth. In the present study, we hypothesized that ATF3 and p53 participate in the process of epilepsy and can affect MFS. To investigate this hypothesis, we examined the expression of ATF3 and p53 in hippocampal tissues of rats kindled by pentylenetetrazole (PTZ) using immunofluorescence, immunohistochemistry and western blotting. MFS was evaluated by Timm staining in the hippocampus. Results from these experiments revealed that expression of ATF3 and p53 is significantly higher (p<0.05) in the CA3 area of the hippocampus in the PTZ-treated group compared to the control group. ATF3 expression gradually increased from 3 days to 4 weeks, peaked at 4 weeks and decreased slightly at 6 weeks in the PTZ group, while the expression of p53 was maintained at similar levels at different time-points following PTZ treatment. No obvious difference in the expression of these proteins was observed between the PTZ and the control group in the dentate gyrus (DG) area (p>0.05). The degree of MFS in the PTZ group peaked at 4 weeks and was maintained at a high level until 6 weeks post-PTZ treatment. In conclusion, ATF3 and p53 may be involved in the occurrence of seizure and play critical roles in MFS in the PTZ kindling model.